The Board's Commitment as a Factor Strengthening the Influence of Board Characteristics on Company Financial Performance - Sukma Agung, Dwi Mas; Chandra, Kristian; Margaretha, Farah; Nalurita, Febria; Purba, Yosephina E (International Journal of Management Science and Information Technology, 2026)
This study examines the effect of board characteristics on financial performance of manufacturing firms listed on the Indonesia Stock Exchange during 2019–2023. Specifically, it investigates the influence of board size, board independence, board expertise, and female board representation on firm performance, while incorporating board commitment as a moderating variable and firm size, firm age, and leverage as control variables. Financial performance is measured using Return on Assets (ROA) and Return on Equity (ROE). The study employs a quantitative research design using secondary data derived from annual reports of 55 manufacturing companies selected through purposive sampling. Panel data regression analysis is conducted using EViews 9. The findings reveal that firm size and firm age positively affect ROA, whereas leverage negatively affects ROA. For ROE, board size, board commitment, and leverage show positive effects, while female board representation, firm size, and firm age demonstrate negative effects. Furthermore, board commitment negatively moderates the relationship between board size and ROE. The results suggest that larger boards may enhance performance through diverse expertise and experience; however, higher female board representation is associated with lower performance within the observed context. This study contributes to corporate governance literature by highlighting the contingent role of board commitment and provides practical implications for corporate governance design and investment decision-making.